Analisis Tarif Suroboyo Bus dengan Metode Willingness To Pay dan BOK - Masliyah; Ekawati, June (Institut Teknologi dan Sains Mandala, 2024)
Public transportation in big cities is very important in carrying out one of its main functions as a carrier for people's movements. For this reason, the Surabaya City Government has operationalized the Suroboyo bus, so it is necessary to conduct research to determine whether the current payment method complies with the Vehicle Operational Cost (BOK) regulations. The method used in this research is Willingness To Pay (WTP). After doing the calculations, the Willingness To Pay (WTP) value on weekdays is Rp. 4,751. This condition indicates that the current tariff for using plastic waste bottles is equivalent to Rp. 5000 so that it is still feasible or in accordance with the Willingness To Pay of Suroboyo Bus passengers. The amount of vehicle operating costs (BOK) incurred by Suroboyo Bus is Rp. 2,982 according to standard regulations of the Surabaya City Transportation Service. In terms of service users, the Suroboyo Bus fare of IDR 5,000 is also not considered burdensome or expensive because the difference between the WTP and the applied rate is not large.